2013
DOI: 10.1111/cdev.12096
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Executive Functioning

Abstract: Although early studies of executive functioning in children supported Miyake et al.'s (2000) three-factor model, more recent findings supported a variety of undifferentiated or two-factor structures. Using a cohort-sequential design, this study examined whether there were age-related differences in the structure of executive functioning among 6- to 15-year-olds (N = 688). Children were tested annually on tasks designed to measure updating and working memory, inhibition, and switch efficiency. There was substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
468
1
32

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 524 publications
(533 citation statements)
references
References 63 publications
32
468
1
32
Order By: Relevance
“…Studies tracking developmental changes in working memory and executive control show clear trajectories between 7-10 years of age, but also that children continue to demonstrate substantial improvement in these abilities beyond age 10, up to adulthood (e.g. Davidson et al, 2006;Lee et al, 2013;Zelazo et al, 2013). As such, these abilities may not be sufficiently developed in our 7-10 year-old sample to enable effective implementation of prioritization.…”
Section: Discussionmentioning
confidence: 88%
“…Studies tracking developmental changes in working memory and executive control show clear trajectories between 7-10 years of age, but also that children continue to demonstrate substantial improvement in these abilities beyond age 10, up to adulthood (e.g. Davidson et al, 2006;Lee et al, 2013;Zelazo et al, 2013). As such, these abilities may not be sufficiently developed in our 7-10 year-old sample to enable effective implementation of prioritization.…”
Section: Discussionmentioning
confidence: 88%
“…A further explanation may be that subtle delays in early childhood may impair the development of executive function, broadly defined as top-down monitoring and control processes that regulate thoughts and behaviour. 40 Impairment in the development of executive function may affect the child's ability to meet increasingly complex cognitive demands. There is some evidence to support this; for example, studies have demonstrated an association between infant attentional control and later cognitive competence, 41 specifically in early ability to maintain attention control 42 and adapt attention to contextual demands.…”
Section: Discussionmentioning
confidence: 99%
“…However, the meta-analysis by Yeniad et al (2013) did not control for other cognitive functions that could explain the associations between shifting and mathematics achievement (Bull & Lee, 2014). In addition, the studies included in the meta-analysis by Yeniad et al (2013) were conducted on children's executive functions, which is of note because there is evidence that measures of executive functions do not clearly separate all executive functions prior to the age of 15 years (Lee, Bull, & Ho, 2013). The role of shifting for academic achievements in adulthood is not yet clear.…”
Section: Relevance Of Executive Functions For Complex Learningmentioning
confidence: 99%